Stress and Support: Determinants of Work-Life Balance for Women Teachers in Private Schools (Journal of Musikot Campus, 2024)
The aim of this study was to find out the role of work stress - work support and family stress - family support in determining the work-life balance of women teachers in private schools of Bhairahawa City. This study is based on a quantitative research approach under the survey research design. The data were analyzed by using descriptive statistics with 201 women teachers selected through convenient sampling approach from 18 private schools. The finding reveals that most women teachers agree that they cannot balance their personal and professional lives smoothly due to the time they have to devote to their jobs. Their personal and family lives distract them from doing their job as good as they can. Additionally, it provides additional information to understand the factors that are essential in determining the work-life balance of women teachers in private schools. Stakeholders, including family heads, and policymakers, should collaborate synergistically to address the underlying causes of stress and provide robust support mechanisms to empower the work-life balance of women teachers.